Knowledge and Attitude of Senior High School Students in Jatinangor towards Sexually Transmitted Infections in 2013 - Hendrana, Aisyah Riseta Aini; Mutyara, Kuswandewi; Rowawi, Rasmia (Althea Medical Journal, 2015)
Background: Sexually transmitted infections (STIs) are major health problem. Until today, the prevalenceÂ of STIs is still high and the incidence is increasing. Almost half of STIs new cases occur in adolescents andyoung adults. It is assumed that there is a positive correlation of knowledge about STIs with attitude andÂ practices; therefore, giving proper information of STIs to adolescents could influence their safe sexualÂ practices, and further, it can prevent STIs to occur. The objective of this study is to discover knowledge andÂ attitude of senior high school students in Jatinangor towards STIs.Methods: This descriptive study was conducted in Sekolah Menengah Atas Persatuan Guru RepublikÂ Indonesia (SMA PGRI) Jatinangor and Sekolah Menengah Atas Negeri (SMAN) Jatinangor from May toÂ September 2013. Questionnaires were completed by 278 respondents selected by stratified cluster randomÂ sampling.Results: More than half respondents had poor knowledge about STIs (56.5%) while 53.2% of the respondentsÂ had positive attitude towards STIs. Most mentioned choices as the information source of STIs were teacher(66.5%), followed by television/radio (45.3%), friends (37.8%), newspaper/magazine (21.2%), motherÂ (16.2%), sibling (7.2%), and father (6.5%).Â Conclusions: More detail information about STIs is needed by adolescents as a way to encourage safe sexualÂ practices. Teacher and parents are expected to be the source information of STIs while mass media can alsobe used to educate adolescents. Education on STIs for teachers is also needed since they are as the mainÂ source for educating the adolescents. [AMJ.2015;2(4):568â74]Â DOI:Â 10.15850/amj.v2n4.655